Sofrimento no trabalho: narrativas de trabalhadores de grandes indústrias do sul fluminense - Corrêa, José Geraldo (2017)
The current research aims to analyse the labour suffering interpretation by workers which act in the technical-operational level of big industries installed in southern Rio de Janeiro state, regarding the impacts on the psychical and psychosocial health of the research subjects. This will be made through the labour social and psychosocial suffering concept discussion, under the specialized bibliography. In this research, the psychical and psychosocial sufferings coming from labour are analysed through the labour clinics streams. The labour clinics objective is the confluence between the psychical and social universe, establishing one proposal of liberalization and acting capacity of the workers, in order to minimize the labour suffering (Bendassolli; Soboll, 2011). In the understanding of the interviewed ones, through discursive fragments, it is comprehended that the labour suffering existence is acknowledged and interpreted over the incapacity to interfere with their creativity and intelligence in the prescribed labour, going under the impossibility to structure themselves as a labour collective and the perverse action of mistreatments.